2014
DOI: 10.1016/j.resp.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adrenal medullectomy on metabolic responses to chronic intermittent hypoxia

Abstract: Obstructive sleep apnea causes intermittent hypoxia (IH) and is associated with insulin resistance and type 2 diabetes. IH increases plasma catecholamine levels, which may increase insulin resistance and suppress insulin secretion. The objective of this study was to determine if adrenal medullectomy (MED) prevents metabolic dysfunction in IH. MED or sham surgery was performed in 60 male C57BL/6J mice, which were then exposed to IH or control conditions (intermittent air) for 6 weeks. IH increased plasma epinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 78 publications
6
12
0
Order By: Relevance
“…Interestingly, a drop in pAKT was prevented by administration of acipimox; however, the overall pAKT quantity was also reduced with acipimox, which warrants caution in interpretation and suggests that regulation of AKT phosphorylation is a complex process with multiple signaling pathways (including apoptosis, proliferation, and glucose metabolism) that converge on this molecule (36). Similarly, the increase in pAKT in adipose tissue with IH exposure, needs to be evaluated in a context of the severe tissue hypoxia that develops during IH exposure (19), which is a proven strong stimulus for pAKT activation (37,38) (25,32). Our study partially supports this hypothesis, because we showed that adipocytes respond to catecholamine stimulation even after prolonged IH exposure.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, a drop in pAKT was prevented by administration of acipimox; however, the overall pAKT quantity was also reduced with acipimox, which warrants caution in interpretation and suggests that regulation of AKT phosphorylation is a complex process with multiple signaling pathways (including apoptosis, proliferation, and glucose metabolism) that converge on this molecule (36). Similarly, the increase in pAKT in adipose tissue with IH exposure, needs to be evaluated in a context of the severe tissue hypoxia that develops during IH exposure (19), which is a proven strong stimulus for pAKT activation (37,38) (25,32). Our study partially supports this hypothesis, because we showed that adipocytes respond to catecholamine stimulation even after prolonged IH exposure.…”
Section: Discussionsupporting
confidence: 74%
“…Finally, sustained adipose tissue hypoxia or activation of hypoxia-regulated signaling pathways can stimulate lipolysis (18,28,29); however, it is worth noting that IH exposure is characterized by distinct cellular and molecular features, which are different from exposure to sustained hypoxia (30,31). Using glycerol release and adipocyte size distribution as functional and morphological indices of adipocyte lipolysis, this study showed that IH exposure stimulated basal lipolysis, thus providing a functional explanation for results seen in previous studies that reported increased plasma FFA levels in patients with OSA and rodents exposed to IH (7,25,32,33). These results demonstrate that lipolysis represents a process regulated by IH exposure in vivo, together with secretion of adipokines or gene expression regulation (4).…”
Section: Discussionsupporting
confidence: 50%
“…We have previously shown acute elevations of serum epinephrine and norepinephrine during sustained hypoxia or IH (40,68) and the effectiveness of adrenal medullectomy (68). Classic studies have defined the metabolic effects of catecholamine stimulation in liver (71), fat (44), and pancreas (63).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore investigated the SNS in mediating IHinduced metabolic changes by administering the ␣-adrenergic antagonist phentolamine or the ␤-antagonist propranolol 10 min before IH exposure. We also performed adrenal medullectomy to examine the role of circulating catecholamines, having previously demonstrated increased epinephrine and norepinephrine following acute sustained hypoxia (40) or IH (68). Figure 6 shows that phentolamine abolished IH-induced hyperglycemia and glucose intolerance without affecting FFA levels.…”
Section: Ih Modelmentioning
confidence: 99%
“…Several studies evaluated liver glucose output and insulin signal transduction in response to IH [11][12][13][14], but did not achieve consistent conclusions. In terms of how IH influences hepatic glucose metabolism and insulin sensitivity, the major proposed mechanism is the systemic activation of sympathetic nervous system in response to IH [11,13,15]. Less attention has been directed towards direct effects of IH on liver cells per se.…”
Section: Introductionmentioning
confidence: 99%